The surface roughness difference between microhybrid and polycrystalline composites after polishing - Eric Priyo Prasetyo; Karlina Samadi; Cecilia Gerda Juliani Lunardhi (Dental Journal (Majalah Kedokteran Gigi), 2008)
Background: One of the success criteria for a composite resin restorative material is the surface roughness that can be achieved through polishing. Considering that there are so many types of composite resin materials on the market, including polycrystalline composites, information on this type of composite’s surface roughness is needed. Purpose: The aim of this laboratory experiment was to compare the surface roughness difference between microhybrid and polycrystalline composite after polishing. Methods: In order to obtain this, a laboratory experiment was done. Four groups of composites were produced, the first two groups consist of microhybrid composite and the second two groups consist of polycrystalline composite. Two groups with the same material were treated with two different treatments as follows: the first group was not finished (the surface is under celluloid matrix), the second group was finished and polished. After these treatments, each sample’s surface was measured using surface roughness measuring instrument and then the Results: were analyzed statistically using independent t-test (α = 0.05). Conclusion: The result showed that after polishing, the surface roughness of polycrystalline composite is lower than that of microhybrid composite.